2017
DOI: 10.1097/md.0000000000005803
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of puerarin injection in curing acute ischemic stroke

Abstract: Background:Previous studies indicated that the puerarin injection has been widely employed in China for the treatment of acute ischemic stroke. We aim to evaluate the efficacy and safety of the puerarin injection for the treatment of acute ischemic stroke.Methods:A systematic literature search was performed in PUBMED, EMBASE, SPRINGER LINK, Scopus, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP Journals Database, Wanfang database and the China Biological Medicine database before November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Recent reports of adverse events associated with Chinese herbal medicines have increased [ 7 ]. For example, the use of herbal remedies containing aristolochic acid has recently been banned in China due to the association with renal toxicity and carcinogenicity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of adverse events associated with Chinese herbal medicines have increased [ 7 ]. For example, the use of herbal remedies containing aristolochic acid has recently been banned in China due to the association with renal toxicity and carcinogenicity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine has been shown to lack side effects in humans at doses up to 7 g/kg per day for seven days (Cruciani, Dvorkin et al 2006) and in similar doses even for up to 2 months (Curran, Morhart et al 2019). Regarding puerarin, a recent meta-analysis has suggested that treatment with up to 500 mg of puerarin per day for 2-3 weeks was not accompanied by severe side effects, while doses of 200 mg have been shown potential in improving the neurological condition following traumatic brain injury (Zheng, Li et al 2017).…”
Section: Safety and Tolerability Of Gsh Precursors And Nrf2 Activatorsmentioning
confidence: 99%
“…evaluated the efficacy and safety of the puerarin injection for the treatment of acute ischemic stroke. They reported that puerarin injection could improve the neurological deficit and decrease the hemorheology index and fibrinogen in patients with acute ischemic stroke [ 153 ]. Their study suggests that puerarin injection may be effective and relatively safe in the clinic for treating acute ischemic stroke [ 153 ].…”
Section: Clinical Use Of Natural Constituents From Chinese Herbal Medmentioning
confidence: 99%